2019
DOI: 10.3390/cancers11020148
|View full text |Cite
|
Sign up to set email alerts
|

Histone Deacetylase Inhibitors and Phenotypical Transformation of Cancer Cells

Abstract: Histone deacetylase inhibitors (HDIs) are a group of potent epigenetic drugs which have been investigated for their therapeutic potential in various clinical disorders, including hematological malignancies and solid tumors. Currently, several HDIs are already in clinical use and many more are on clinical trials. HDIs have shown efficacy to inhibit initiation and progression of cancer cells. Nevertheless, both pro-invasive and anti-invasive activities of HDIs have been reported, questioning their impact in carc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
71
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(74 citation statements)
references
References 129 publications
3
71
0
Order By: Relevance
“…HDACs are being considered as therapeutic targets for cancer treatment. An array of natural and synthetic compounds inhibiting HDAC activity, referred to as HDAC inhibitor (HDACi), have been developed [10,11,12]. Although increased histone acetylation by HDACi treatment has been observed, this phenomenon could not be linked to therapeutic outcome.…”
Section: Introductionmentioning
confidence: 99%
“…HDACs are being considered as therapeutic targets for cancer treatment. An array of natural and synthetic compounds inhibiting HDAC activity, referred to as HDAC inhibitor (HDACi), have been developed [10,11,12]. Although increased histone acetylation by HDACi treatment has been observed, this phenomenon could not be linked to therapeutic outcome.…”
Section: Introductionmentioning
confidence: 99%
“…The human HDAC family consists of 18 proteins divided into 4 classes. These proteins modulate, among others, the transcription of genes encoding proteins involved in carcinogenesis [57].…”
Section: Inhibitors Of Histone Deacetylase (Hdac)mentioning
confidence: 99%
“…HDACs have been linked to oncogenesis through multiple mechanisms, to date it is known that there is more than one mechanism through which HDACs play their role in carcinogenesis. Many studies demonstrated that both through over-expression [27,28,29,30,31,32] or aberrant interaction with transcriptional regulators [33,34,35,36] HDACs mediate the transcriptional repression of oncosuppressor genes [27,28,29,30,31,33,34,35,36]. Furthermore, different HDACs have shown to have cell context specific roles and to play different pro or anti-cancer activity depending on tumor type.…”
Section: Hdac Proteinsmentioning
confidence: 99%
“…Furthermore, different HDACs have shown to have cell context specific roles and to play different pro or anti-cancer activity depending on tumor type. The differential role of HDACs and the implication of HDAC targeting depending on the context have been extensively reviewed by Wawruszak et al [36].…”
Section: Hdac Proteinsmentioning
confidence: 99%